Composición florística y estructura de un bosque húmedo premontano en el Valle Central de Costa Rica - Cascante M, Alfredo (2001)
The floristic composition and structure of a premontane moist forest remnant were studied in the El Rodeo Protected Zone, Central Valley of Costa Rica. Three one-hectare plots were established in the non-disturbed forest, and all trees with a diameter at breast height (dbh) of 10 cm or greater were marked, measured and identified. The plots were located within a radius of 500 m from each other. A total of 106 tree species were recorded in the three plots. Average values: species richness 69.6 species ha-1, abundance 509 individuals ha- 1, basal area 36.35 m2 ha-1. Total diversity was 3.54 (Shannon Index, H’), and the species similarity among the plots ranged between S=0.68 and 0.70 (Sørensen Similarity Index). Most tree species are represented by few individuals (five or less). There is a lack of emergent trees and arborescent palms in the forest canopy. According to the Familial Importance Value, Moraceae, followed by Fabaceae, Lauraceae, and Sapotaceae, largely dominates this forest. Pseudolmedia oxyphillaria (Moraceae) is the dominant species (Importance Value Index), accounting for 25% of all the marked trees in the plots, followed by Clarisia racemosa (Moraceae), Heisteria concinna (Olacaceae), and Brosimum alicastrum (Moraceae). The size class distributions were similar among plots, and in general followed the expected J-inverted shape. Differences in tree abundance, floristic composition, and spatial distribution of some species among the plots suggest heterogeneity of this ecosystem’s arborescent vegetation. Moreover, it is an important natural reservoir for the conservation of rare and endangered tree species in a national level. Using these results as a baseline, this study should start a long term monitoring of the structure and composition of this very reduced and fragmented ecosystem.